If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4y + 1) = 4(2 + -2y) + -10 Reorder the terms: -2(1 + 4y) = 4(2 + -2y) + -10 (1 * -2 + 4y * -2) = 4(2 + -2y) + -10 (-2 + -8y) = 4(2 + -2y) + -10 -2 + -8y = (2 * 4 + -2y * 4) + -10 -2 + -8y = (8 + -8y) + -10 Reorder the terms: -2 + -8y = 8 + -10 + -8y Combine like terms: 8 + -10 = -2 -2 + -8y = -2 + -8y Add '2' to each side of the equation. -2 + 2 + -8y = -2 + 2 + -8y Combine like terms: -2 + 2 = 0 0 + -8y = -2 + 2 + -8y -8y = -2 + 2 + -8y Combine like terms: -2 + 2 = 0 -8y = 0 + -8y -8y = -8y Add '8y' to each side of the equation. -8y + 8y = -8y + 8y Combine like terms: -8y + 8y = 0 0 = -8y + 8y Combine like terms: -8y + 8y = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3/8*16 | | 8y-2=8-8y-10 | | 8x+(1.5x*4)=600 | | 9x^2=30x-24 | | 6=3/5u | | -6x-27=-x^2 | | 7-9x+8=-6x-(-7x+x) | | x^2-7x-16=-3x | | x^2+11x+22=0 | | x^2+11x+32=2 | | (14x-7)= | | (3x^4y^-5/9x^-6y^8)^-3 | | 3x-4+2(2x)+17=-3-2x+(16-6) | | x^2-2y-8=0 | | 3/4/4/9 | | 4x-39=8x-19 | | a11/a6 | | 4*4*4*4*4*4*4*4*4*4= | | 2x+18=78 | | (T/7)=2 | | -7(8)*-56-(-4)(-9)= | | 5(x+3)+(x-2)2=39 | | 18/x=252 | | 3d+9=37 | | x/18=182 | | 6m-9=15+2m | | x^(-5/3) | | -7(8)*2-(-4)(-9)= | | x^-5/3 | | 4n-2=-7+5n | | U=cn | | u=cb |